consideration of the Buddhist monks’ samaṇasāruppa - ปิยปัญญาวงศ์ อัญชลี; กาญจนพิศศาล สุปรียส์ (Journal of Buddhist Studies Chulalongkorn University, 2019)
This article aims to study the concept of samaṇasāruppa and the criteria for considering the samaṇasāruppa of Buddhist monks. The study finds that the term “samaṇasāruppa” refers to a set of criteria which consider not only bodily and verbal expressions (external samaṇasāruppa) but, more importantly, also mental qualities (internal samaṇasāruppa) of Buddhist monks, especially those of noble persons (ariyapuggala). If a Buddhist monk can attain internal samaṇasāruppa or virtues fitting a monastic person, the external samaṇasāruppa will follow spontaneously. In principle, laypersons may consider both internal and external samaṇasāruppa of monks. The criterion for considering internal samaṇasāruppa is the level of monks’ mental ability in eliminating fetters (saṁyojana). The consideration of the external samaṇasāruppa has to refer to precepts and practical traditions of Buddhist monks. In the case of the complex actions, one should also refer to the 4 groups of basic criteria which facilitate monks’ attainment of the ultimate goal of Buddhism. These include: 1) Being easy to support, 2) Wanting little, being content, and not hoarding, 3) Being fond of solitude, free of defilements, and respectable, and 4) Being secluded and exerting. In practice, although laypersons can consider the external samaṇasāruppa of Buddhist monks, it is more difficult to consider their internal samaṇasāruppa due to two limitations. These are: 1) the epistemic limitation in determining whether a monk is a noble person, and if so, at which level, and 2) the limitation of knowledge of the Buddhist monks’ codes of monastic disciplines. Therefore, in considering the samaṇasāruppa of Buddhist monks, a laity should keep these two limitations in mind. Besides, such consideration should be done without bias for the sake of cautiousness and fairness, which will in the end benefit the development of Buddhist monk’s samaṇasāruppa.